1994
DOI: 10.1001/archopht.1994.01090190022012
|View full text |Cite
|
Sign up to set email alerts
|

Macular Hole Following Severe Hypertensive Retinopathy

Abstract: In both patients, no tissue growth factor was used to pharma¬ cologically assist in the closure of the macular hole. Although these two patients represent a limited experi¬ ence, patients with proliferative dia¬ betic retinopathy and a macular hole may have a poorer visual prognosis after hole closure than patients with idiopathic macular hole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
2
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 3 publications
0
8
2
1
Order By: Relevance
“…2,3 The vitreous hemorrhage or exudation from the disc or retinal vessels could have induced contraction of the posterior vitreous cortex with subsequent tangential and/or anteroposterior vitreous traction on the fovea. Structural damage from edema, hemorrhage, and ischemia may have weakened the fovea and resulted in the formation of the macular hole.…”
Section: Commentmentioning
confidence: 99%
“…2,3 The vitreous hemorrhage or exudation from the disc or retinal vessels could have induced contraction of the posterior vitreous cortex with subsequent tangential and/or anteroposterior vitreous traction on the fovea. Structural damage from edema, hemorrhage, and ischemia may have weakened the fovea and resulted in the formation of the macular hole.…”
Section: Commentmentioning
confidence: 99%
“…Although most macular holes are idiopathic, they are occasionally associated with trauma, high myopia, and retinal vascular diseases such as proliferative diabetic retinopathy [1], hypertensive retinopathy [2], and congenital retinal arteriovenous communication [3]. A few studies have reported that rupture of a retinal arterial macroaneurysm might result in macular hole formation [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…MHs are also rarely associated with retinal vascular disease, such as proliferative diabetic retinopathy,5 hypertensive retinopathy6 and congenital retinal arteriovenous communication 7 8. With respect to retinal arterial macroaneurysm, only a few cases of MH associated with the rupture of a macroaneurysm have been reported 8 9 10 11 12 13.…”
mentioning
confidence: 99%